World Bank-Financed HIV Projects in the Caribbean : Lessons for Working with Small States - Carpio, Carmen; De Geyndt, Willy; Chao, Shiyan (World Bank, Washington, DC, 2017)
This paper summarizes the key findings of an 'After Action Review' (AAR) that reflects a decade of experience in designing and implementing ten HIV/AIDS projects in the Caribbean, financed by the World Bank. The objective is to identify what worked (and what didn't) in the project approach, design and implementation, distilling useful lessons for other projects in small states.